Quantitative Precursory Information of Weak Shocking Failures of Composite Soft Roof - Lihua Wang; Zenghui Zhao; Zhongxi Tian; Wei Sun (Shock and Vibration)
To reveal the mechanism of weak roof shocking in mine roadway arranged in weakly consolidated soft rock strata commonly observed in western China, a bearing system of composite roof composed of weakly consolidated soft rocks and coal layers was proposed. Then, theoretical analysis and numerical calculation were applied for instability failures of the mass bearing system with strong body and weak body. Eventually, precursory information and criteria of instability failures of the bearing system were developed. The main conclusions obtained are as follows: (1) as the elastic energy released at the postpeak failure stage of weak body contributes to system failures, the equivalent stiffness for system failures consists of the stiffness of strong body and the deterioration stiffness of weak body at softening stage; (2) during the loading process of the two-body system, isochronous sudden jumps of the deformation rate in either body can be regarded as the precursory information of weak impact failures; (3) the frequency of sudden jumps of deformation rate is significantly related to the stiffness, indicating that weak impact failures are readily observed in composite soft roof as stiffnesses of weakly consolidated soft rocks and coal seam are close to each other. This study provides references for prevention and control of weak shocking disasters of composite roofs in western China.